Translator behaviour criticism and Chinese folk language translation: a case study of Bronze and Sunflower - Nie, Zhixing; Kaur, Hardev (SAGE Publications, 2025)
The translation of the Chinese folk language plays a vital role in preserving cultural authenticity and shaping the distinctive style of Chinese children’s literature. This study employs Zhou Lingshun’s theory of Translator Behaviour Criticism to examine Helen Wang’s English translation of Cao Wenxuan’s Bronze and Sunflower (2015/2005), with a specific focus on the translation of folk language elements such as dialects, colloquialisms, idioms, and set phrases. By focusing on translating dialect words and idiomatic expressions, this research examines how the English version reconstructs the original’s stylistic features, including its emotional depth, cultural context, and aesthetic tendencies. The findings reveal notable challenges in representing dialects, encapsulating local cultural nuances and conveying character identity and emotional tone. While some of Helen Wang’s translations achieve functional equivalence, others dilute the authenticity of the source text by opting for standard English or omitting culturally loaded terms. Similarly, the translation of idiomatic expressions, integral to the narrative’s humour and local flavour, often needs help to balance literal meaning with the expressive and aesthetic functions of the original. This results in the loss of natural simplicity and vibrancy inherent in the folk language. This study proposes that in translating folk language for children’s literature, translators should strive to balance fidelity to the original’s folk characteristics (“seeking truth”) with the practical needs of target readers (“seeking utility”). Such an approach ensures cultural authenticity while meeting the reading expectations of child audiences, ultimately creating translations that effectively convey the richness of the original work.